THE INFLUENCE OF COMPETENCE ON EMPLOYEE PERFORMANCE AT CLASS IIA CORRECTIONAL INSTITUTION IN SUMBAWA BESAR - Apriani, Winda Andi; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2025)
To assist public sector organizations in improving productivity, it is essential to ensure that their employees possess the appropriate qualifications and competencies, one way being to enhance each employee's competence. The objective of this writing is to determine the competence, performance, and the influence of competence on employee performance at the Class IIA Correctional Institution in Sumbawa Besar. This research was conducted using a quantitative research method. The results show that employees at the Class IIA Correctional Institution in Sumbawa Besar have a fairly good perception of their performance and work competencies. There is a positive influence of work competence on employee performance at the Class IIA Correctional Institution in Sumbawa Besar. Keywords: Performance; Competence; Management; Human Resources